Systematic significance of pollen morphology in rare endemic taxa of Astragalus L. (Fabaceae) - Khan, Amjad; Ahmad, Mushtaq; Zafar, Muhammad; Shah, Sayed Afzal; Rozina (Phytotaxa, 2022)
Pollen grains were studied for ten species of Astragalus L. endemic to Pakistan, by using light and scanning electron microscopy with the aim of extending the knowledge of their morphology and investigating whether pollen morphology can help in the identification and delimitation of controversial taxa. Consequently, we observed qualitative characters of pollen grains that ranged from small to medium, radially symmetrical, prolate to sub-prolate, trizonocolporate to tricolporate; granulate to scabrate and isopolar in all taxa. While the surface sculpturing among the species varied from perforate to granulate, reticulate to microreticulate, reticulate, perforate to reticulate, microreticulate to perforate and perforate. Similarly, among the quantitative parameters, maximum polar diameter was recorded in A. brahuicus (36.25 μm) and minimum in A. amherstianus (18.33 μm) while the equatorial diameter was maximum in A. stocksii (25.41 μm) and minimum in A. amherstianus (18.33 μm). The P/E ratio was recorded maximum in A. amherstianus (1.56 μm). Thus, length and width of colpi was maximum in A. purpurascens (26.25 μm) and A. hostilis (4.16 μm), along with the length and width of pore maximum in A. psilacanthus (8.75 μm) and A. chorizanthus (14.21 μm) respectively. We also observed the maximum value of mesocolpium and exine thickness in A. brahuicus (26.25 μm) and A. stocksii (2.04 μm). Furthermore, for easy and fast identification of studied taxa, diagnostic key was established based on examined parameters. However, the study addresses about the PCA, PCoA and UPGMA were recognized for relationships among the species based on studied pollen characters.